Five-Month Follow-Up Assessing Defecography and Urodynamics after Laparoscopic Nerve-Sparing Colorectal Resection for Endometriosis - Claudio Peixoto Crispi; Claudio Peixoto Crispi; Alice Cristina Coelho Brandão Salomão; Claudia Maria Vale Joaquim; Bruna Rafaela Santos de Oliveira; Marlon de Freitas Fonseca (Case Reports in Obstetrics and Gynecology)
Introduction. Large resections may be necessary in cytoreductive surgery for endometriosis, which present risk of urinary and bowel complications. Presentation of Case. A 29-year-old woman underwent multidisciplinary laparoscopy for endometriosis in a private practice setting for acyclic pelvic pain and cyclic abdominal distension with changes in bowel habits and frequent sensation of incomplete defecation. After surgery, urodynamics remained normal and bowel function improved subjectively and objectively per dynamic magnetic resonance defecography (DMRD). The five-month follow-up found improvements in pain scores, bowel function, and health-related quality of life (assessed by the full versions of the Short Form 36 and Endometriosis Health Profile 30 scales). Discussion. Animus may contribute to the bowel symptoms in women with endometriosis. DMRD provides additional objective parameters for comparing pre- and postoperative functions. Conclusion. A nerve-sparing segmental rectosigmoidectomy for endometriosis carefully executed by a multidisciplinary team can preserve the function of different pelvic organs.